2013
DOI: 10.1007/s00216-013-7428-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity of lateral flow immunoassay for ochratoxin A through silver enhancement

Abstract: Silver nucleation on gold has been exploited for signal amplification and has found application in several qualitative and quantitative bio-sensing techniques, thanks to the simplicity of the method and the high sensitivity achieved. Very recently, this technique has been tentatively applied to improve performance of gold-based immunoassays. In this work, the exploitation of the signal amplification due to silver deposition on gold nanoparticles has been first applied to a competitive lateral flow immunoassay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 30 publications
0
70
0
1
Order By: Relevance
“…It was also demonstrated that AuNPs can be used not only for biocompounds detection (Karakus, 2015); toxins (Anfossi et al, 2012(Anfossi et al, , 2013B.H. Liu et al, 2014;C.…”
Section: Designed a Lfsmentioning
confidence: 94%
See 1 more Smart Citation
“…It was also demonstrated that AuNPs can be used not only for biocompounds detection (Karakus, 2015); toxins (Anfossi et al, 2012(Anfossi et al, , 2013B.H. Liu et al, 2014;C.…”
Section: Designed a Lfsmentioning
confidence: 94%
“…Furthermore, LFBs are not limited only to biomolecules detection; several publications have appeared in the last years about the detection of pollutants such as metallic ions, pesticides, etc. The range of LFBs applications is including detection of hazardous substances (Shyu et al, 2002), heavy metals in drinking waters (Mazumdar et al, 2010;Torabi and Lu, 2011;Kuang et al, 2013;López-Marzo et al, 2013a, allergens and pathogens in food Shukla et al, 2011;Preechakasedkit et al, 2012;Leem et al, 2014;Berlina et al, 2013;Anfossi et al, 2012Anfossi et al, , 2013, pesticides (Zhou et al, 2004;Kim et al, 2011;Wang et al, 2014a), drugs screening (Inoue et al, 2007), etc.…”
Section: Lateral Flow Biosensors (Lfbs)mentioning
confidence: 99%
“…To overcome this limitation, researchers have worked on different labeling tags, including silver or gold enhancement (Anfossi et al, 2013;Hu et al, 2013), chemiluminescent tags or fluorescent tags (Zou et al, 2010;Berlina et al, 2013;Bruno, 2014;Taranova et al, 2015), magnetic nanoparticles Wang et al, 2013), and carbon nanoparticles (Noguera et al, 2011). Anfossi et al (2013) amplified the detection signal of an ochratoxin by using a detection LFTS that utilizes silver nucleation on gold nanoparticles. The signal enhancement based on the silver deposition on gold nanoparticles improved the sensitivity by 10-fold compared to the gold-based LFTS.…”
Section: Labeling Tagsmentioning
confidence: 99%
“…Due to low abundance of targets, high sensitivity is highly desired for LFBs. An effective way for improving the sensitivity of the GNPs-based bioassay is to amplify the Au signal by adopting silver enhancement technology to the traditional bioassay [75][76][77][78][79][80][81]. Under the action of the reducing agent, silver ions is prone to gather around the GNPs in the form of silver, the color of the test zone is greatly enhanced due to the silver deposition on the GNPs surface.…”
Section: Signal-amplification Strategiesmentioning
confidence: 99%